KAJIAN PERBEDAAN KATALIS DAN MEMINIMALISIR WAKTU DALAM PEMANFAATAN LIMBAH CAIR KELAPA SAWIT MENJADI BIODIESEL - Purnamasari, Juita; Anggraini, Widya; Herdiansah, Riko (Program Kreativitas Mahasiswa - Penelitian, 2013)
The purpose of this study is to assess the quantity and quality of the biodiesel produced using ultrasonic technology with an acid catalyst and modification time. The raw material in this study is the oil fraction from palm oil processing wastewater. In the esterification process used two variations of the addition of an acid catalyst. The results showed the use of ultrasonic techniques with 0.5% H2SO4 catalyst with a time of 25 minutes and the temperature of 600C can produce a higher yield compared to other treatments. So also was able to meet the quality of SNI 04-7182-2006 for quality parameters density, viscosity, cetane number, cloud point and the number odium.Â Keywords: methyl ester, fraction of palm oil from waste water, ultrasonic technology